A bouncy house? UK select committee newsworthiness, 2005–18. Issue 3 (3rd July 2019) - Gaines, Brian J.; Goodwin, Mark; Bates, Stephen Holden; Sin, Gisela
ABSTRACT: Traditionally, legislative committees have been regarded as quite unimportant in the UK. Some scholars contend that recent reforms have substantially increased the powers of select committees, rendering them genuinely important to policy and the scrutiny of government; others see little sign of change. We examine House of Commons select committees in regard to exactly one indicator of significance, their newspaper coverage. We detect significant gains in salience of some committees, as compared to the period just before the Wright reforms (2005–10). But committees vary dramatically in coverage levels and trends, and it is unclear if their newspaper profiles continue to grow.